Hybrid gum tragacanth/sodium alginate hydrogel reinforced with silver nanotriangles for bacterial biofilm inhibition. Issue 10 (26th November 2022) - Garg, Deepa; Matai, Ishita; Agrawal, Shruti; Sachdev, Abhay
Abstract: Biomaterial associated bacterial infections are indomitable to treatment due to the rise in antibiotic resistant strains, thereby triggering the need for new antibacterial agents. Herein, composite bactericidal hydrogels were formulated by incorporating silver nanotriangles (AgNTs) inside a hybrid polymer network of Gum Tragacanth/Sodium Alginate (GT/SA) hydrogels. Physico-chemical examination revealed robust mechanical strength, appreciable porosity and desirable in vitro enzymatic biodegradation of composite hydrogels. The antibacterial activity of AgNT-hydrogel was tested against planktonic and biofilm-forming Gram-negative ( Escherichia coli and Pseudomonas aeruginosa ) and Gram-positive ( Staphylococcus aureus ) bacteria. For all the strains, AgNT-hydrogel showed a dose-dependent decrease in bacterial growth. The addition of AgNT-hydrogels (40-80 mg ml −1 ) caused 87% inhibition of planktonic biomass and up to 74% reduction in biofilm formation. Overall, this study proposes a promising approach for designing antibacterial composite hydrogels to mitigate various forms of bacterial infection. GRAPHICAL ABSTRACT: UF0001